Goodword islamic studies grade 5 - Khan, Saniyasnain (Goodwords; New Dehli, 2022)
"Goodword Islamic Studies: Grade 5" by Saniyasnain Khan provides a comprehensive introduction to Islamic teachings, values, and history tailored for young learners.